The role of a short post-lunch nap in improving cognitive, motor, and sprint performance in participants with partial sleep deprivation - Waterhouse, J.; Atkinson, G.; Edwards, B.; Reilly, T. (Journal of Sports Sciences, 2007)
The aim of this study was to determine the effects of a post-lunch nap on subjective alertness and performance following partial sleep loss. Ten healthy males (mean age 23.3 years, s = 3.4) either napped or sat quietly from 13:00 to 13:30 h after a night of shortened sleep (sleep 23:00 - 03:00 h only). Thirty minutes after the afternoon nap or control (no-nap) condition, alertness, short-term memory, intra-aural temperature, heart rate, choice reaction time, grip strength, and times for 2-m and 20-m sprints were recorded. The afternoon nap lowered heart rate and intra-aural temperature. Alertness, sleepiness, short-term memory, and accuracy at the 8-choice reaction time test were improved by napping (P < 0.05), but mean reaction times and grip strength were not affected (P > 0.05). Sprint times were improved. Mean time for the 2-m sprints fell from 1.060 s (s = 0.018) to 1.019 s (s = 0.019) (P = 0.031 paired t-test); mean time for the 20-m sprints fell from 3.971 s (s = 0.054) to 3.878 s (s = 0.047) (P = 0.013). These results indicate that a post-lunch nap improves alertness and aspects of mental and physical performance following partial sleep loss, and have implications for athletes with restricted sleep during training or before competition.